The effect of sliding velocity on the dry sliding wear of nanophase Fe30Ni20Mn25Al25 against yttria-stabilized zirconia. (April 2017) - Lu, Y.; Baker, I.; Kennedy, F.E.; Munroe, P.R.
Abstract: In order to investigate the influence of the temperature increase due to frictional heating on the wear behavior of the nanostructured alloy Fe30 Ni20 Mn25 Al25, which consists of alternating b.c.c. and B2 phases with interfaces aligned along 〈100〉, dry sliding pin-on-disk tests were conducted in air at several sliding velocities (0.1 m s −1, 0.25 m s −1, 0.5 m s −1, 0.75 m s −1 and 1 m s −1 ) for 1 km. Disks of yttria-stabilized zirconia were used as the counterface. A combination of state-of-the-art techniques was used to characterize the pins, disks and debris after wear tests. It was found that the pins had much higher wear rates at a lower sliding velocity compared to a higher sliding velocity, although the wear rate of the zirconia counterface was higher at the higher sliding velocities. It was concluded, based on X-ray diffraction and transmission electron microscopy, that the increase in zirconia wear at higher sliding velocities was due to localized phase transformation of the zirconia caused by high frictional contact temperatures. The zirconia debris removed from the disk because of the phase transformation also contributed to the lower mass loss of the pins in wear tests at sliding velocities of 0.5 m s −1 or higher because zirconia embedded in the surface of the pins provided added protection against pin wear. Highlights: Wear rates at low sliding velocities were much higher than at higher velocities. Contact temperature was responsible for lower wear at higher sliding velocities. Oxidation and hard mechanically-mixed layers provided protection against wear. Mechanically-mixed layers on the worn pin surfaces contained zirconia. Wear rate of the zirconia counterface disk was higher at higher velocities.